2014
DOI: 10.2474/trol.9.184
|View full text |Cite
|
Sign up to set email alerts
|

PFPE Lubricant Molecular Weight Effects on Slider-Disk Interactions

Abstract: Slider wear is investigated as a function of D-4OH lubricant film thickness and molecular weight. Slider wear increases with decreasing lubricant film thickness and with increasing molecular weight when compared at the same film thickness in the submonolayer film thickness regime. The two sets of observations are readily interpreted on the basis of the monolayer fraction which corrects the film thickness for the molecular weight-dependent surface coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Depending upon the read-write duty cycle, the mobility of the boundary lubricant film, and the local supply of the lubricant film, reflow from the surrounding area into the thickness-depleted area may, or may not, occur at a fast enough rate to maintain tribological robustness under HAMR conditions. Many recent tribological studies indicate that lubricant coverage is the significant determinant for contamination robustness and head-disk interface reliability [12][13][14][15]. Tribological robustness must still be satisfied in the HAMR interface.…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the read-write duty cycle, the mobility of the boundary lubricant film, and the local supply of the lubricant film, reflow from the surrounding area into the thickness-depleted area may, or may not, occur at a fast enough rate to maintain tribological robustness under HAMR conditions. Many recent tribological studies indicate that lubricant coverage is the significant determinant for contamination robustness and head-disk interface reliability [12][13][14][15]. Tribological robustness must still be satisfied in the HAMR interface.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the average film thickness for n = 4 is thinner than n = 1.5 and 3 samples (Table 2) and as a result could additionally contribute to the observed larger slider wear rate. In sub-monolayer PFPE applications, slider wear has been shown to scale with thickness for the same PFPE and with coverage for identical PFPE film structures having different molecular weights [8]. Here the molecular weights are nearly identical but the main chain structures are different and the film thickness for n = 4 is slightly lower ( Table 2).…”
Section: Discussionmentioning
confidence: 88%
“…3. Slider wear as a function of overpush was recently published so no Table 3 Lube extensive reiteration is necessary here [8]. After the continuous sliding experiment is completed (15 min duration), the slider is brought back to the reference track where the touchdown power is re-measured.…”
Section: Methodsmentioning
confidence: 99%
“…Some recent related studies have also shown that HDD tribological data could be more readily interpreted on the basis of PFPE film coverage, as quantified by the monolayer fraction. 22,23 Referring next to Figure 8b, we have plotted siloxane counts as a function of monolayer fraction for ZTMD and D-4OH. Unlike Figure 8a, the two PFPEs do not fall on the same curve indicating that PFPE type is also a significant determinant.…”
Section: ■ Results and Discussionmentioning
confidence: 99%